A Case of Vesicocervical Fistula - Saha, Mukti Rani; Begum, Masuda; Chowdhury, Md. Shafiqul Alam; Ara, Iffat (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 226-228 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15363